PERAN KOMITE SEKOLAH DALAM MENINGKATKAN MUTU PENDIDIKAN DI PONDOK PESANTREN MODERN TERPADU TUANKU LINTAU KABUPATEN TANAH DATAR - Laminsar Laminsar (IAIN Batusangkar, 2016)
Peran komite sekolah dalam meningkatkan mutu pendidikan di pondok pesantren modern terpadu tuanku lintau kabupaten tanah datar. This research intent for revealing problem that gets bearing with schooled committee role in upgrade education quality at at Intergraited Muslim Boarding School Modern of Tuanku Lintau. To get observational problem answer that therefore formulated 4 focus sub that will be tested (1 ) Committee Role as Giving As judgments (2) Committee Role as Supporting As (3 ) Committee Role as Supervisor (4 ) Committee Role as Mediator. Respondent in research is integraited muslim boarding school headmaster of tuanku Lintau and therewith chairman governing Intergraited Muslim Boarding School Modern of Tuanku Lintau. whereas data collecting tech with observation, interview and studi documents gather trick data with data reduction, data representation, conclusion pull or analyzedThat analyzed point out result committee role in upgrade education quality intergraited muslim boarding school modern of tuanku Lintau stills was maximal because of a lot of administrator and member that don’t active, but although is role such committee makes a abode to walk both as judgment giver, supporting, supervisor and as mediator so gets implication to medium development velocity and utilised premedium education upgrade at intergraited muslim boarding school modern of tuanku Lintau.Kata Kunci:Komite Sekolah, meningkatkan mutu